PEGON-GLIPH GAME PENGENALAN DAN PEMBELAJARAN ARAB PEGON BERBASIS ANDROID - Lukman Hakim Wijaya; Ismail Abdurrazzaq Zulkarnain; Khoiru Nurfitri (KOMPUTEK, 2021)
This study aims to design an Android-based game as a medium for the introduction and learning of Arabic pegon and to evaluate user performance of the Arabic pegon educational game using the User Experience Questionnaire (UEQ). The research stages consisted of stages, 1) research data; 2) design; 3) implementation; 4) examiners; 5) report creation. Then the design of this product is in the form of a Pegon-gliph game which is run on the Android system by having four main features, namely material features, training features, game features, and motivation features. And UEQ benchmark test results get good scores in the novelty category, while in other categories such as attractiveness, visibility, efficiency, dependability, and stimulation, the results are very good. So that the results of the performance of the Pegon-gliph educational game users show a positive user impression.